Self-sensing cement composites for structural monitoring: Behaviour under cyclic loading - Mendoza Reales Oscar; José Aguiar Junior Claudio; de Almeida Carísio Pedro; Teodósio Soares Carlos Fernando; Toledo Filho Romildo (MATEC Web of Conferences)
The use of electrically conductive nanomaterials, such as carbon nanotubes (CNT), has been shown to transform cement-based composites into self-sensing cement composites (SSCC) with inherent monitoring capabilities. These composites detect strain through piezoresistive response by measuring changes in electrical resistance caused by mechanical loading. As a result, SSCC can be calibrated for use as sensors in concrete structures. However, due to their brittle nature, it remains unclear whether the electrical properties of SSCC remain constant after repeated mechanical loading. This study investigates the electrical response of SSCC fabricated with two CNT concentrations (0.50% and 1.00% by mass of cement) and subjected to varying sonication energies (5.5 kJ/gCNT, 27.5 kJ/gCNT, and 110 kJ/gCNT) in an aqueous medium. Cubic samples with embedded copper electrodes were prepared and cured for 28 days. After curing, the samples were dried and fitted with two strain gauges each. Compressive loading was applied in seven incremental regimes, ranging from 2 MPa to 40 MPa, with three loading cycles per regime. During the loading process, strain was recorded using the strain gauges, while electrical resistivity was measured through the copper electrodes, both monitored via a data acquisition system. The results revealed that all samples exhibited similar compressive strengths, irrespective of sonication energy or CNT concentration. In contrast, the elastic modulus increased with higher CNT concentrations and greater sonication energies. Under cyclic loading, all samples demonstrated linear behaviour up to the 10 MPa regime. It was concluded that SSCC calibration was preserved during cyclic loading within the elastic deformation range.